Analisis Pemilihan Supplier dengan Menggunakan Metode Analitical Hierarchy Process Unit Repair Management & Partnership pada PT. ABC - Sinahartuti, Beladien; Mauliddina, Yasmin; Ranti, Gadih; Herlambang, Mega Bagus (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Selecting the right supplier is crucial to ensure project quality and smooth operations. This study aims to determine the best supplier for the Remaining Life Analyst Turbine GE Frame 5 Project at PT. ABC by applying the Analytical Hierarchy Process (AHP) method. The assessment criteria used include Price, Quality, Delivery Time, and Payment Terms, which were then compared for three candidate suppliers: PT.123, PT.456, and Yayasan 789. Based on the AHP analysis results, the Payment criterion was identified as the most influential factor. From the global priority calculations, PT.456 emerged as superior and was determined as the selected supplier. These results demonstrate that the AHP method is effective as a decision-support tool for complex decisions, providing an objective and structured recommendation for selecting the company's strategic partners.